Predicting dispersion of radionuclides through parallel approach. (2018) - Maheswari, G. Uma; Subha, S.
Radiation release from the accidents of nuclear power plant (NPP) may likely to cause harmful impacts on the individuals and the environment. The discharge of radionuclides and climatic diffusion causes harm to air, water, plants, animals and soil. Mechanism that helps in predicting radionuclides in air will guide individuals to clear from tormented zones. In order to perceive radioactive material dissipation and its outcome in the atmosphere, it is necessary to understand climatic scattering process information about source term (nuclear material released), atmosphere conditions and geographical parts. The climatic scattering framework integrates source, wind field, scattering and dosages counts. This work completely utilises PC to calculate the toxin scattering in the atmosphere. The thought behind is to create parallel calculations giving subtle elements on parallelism of the solver. The calculation is also implemented using C programming.